Troubling freedom : Antigua and the aftermath of British emancipation - Lightfoot, Natasha, 1978- (Duke University Press, 2015)
Natasha Lightfoot tells the story of how Antigua's newly freed black working people struggled to realize freedom, prior to and in the decades following their emancipation in 1834. Their continued efforts in the face of oppression complicate common definitions of freedom and narratives about newly freed slaves in the Caribbean.